Integrated simulation test platform of operation control system for high-speed maglev transport - WANG Zhiwei; LI Jinglan; QI Yuanjing; FANG Kai (机车电传动)
This paper proposed an implementation solution to build an integrated simulation test platform by combining digital simulation with physical interface equipment according to the overall requirements of collaborative simulation test and integrated test of the operation control system for high-speed maglev transport. In consideration of the characteristics, composition and basic principles of high-speed maglev transport systems, the dynamics and kinematics model of maglev trains was associated with the traction system model of the corresponding partition of the target track model by the corresponding partition attributes into a vehicle-ground interaction correlation model. Taking this correlation calculation model as the core, a semi-physical simulation test environment was established, including a vehicle system model, on-board operation control interface and partition operation control interface, which was connected to the equipment of the tested operation control system to form a closed-loop test system. In addition, the vehicle-ground wireless communication was simulated by networking via wired LAN, which created an internetworking test environment for the integrated simulation test of the operation control system for maglev transport. The experimental application in the actual project proves that the test platform with complete, reasonable and effective simulation functions can provide a test and verification environment with all-around functions and high-degree simulation for the operation control system of high-speed maglev transport.